Psychological Climate, Catharsis, Organizational Anomie, Psychological Wellness and Ethical Procurement Behaviour in Uganda's Public Sector - Mpeera Ntayi, Joseph; Ahiauzu, Augustine; Eyaa, Sarah (Journal of Public Procurement, 2011)
The purpose of this study is to investigate the relationship between psychological climate, catharsis, organizational anomie, psychological wellness and ethical procurement behaviour in Uganda's public sector, in order to understand better the conditions that foster or diminish procurement ethics in a developing country. Data for this study were collected from a sample of 1100 respondents out of which 460 usable questionnaires, representing a 42% response rate were received and analyzed. Results reveal that psychological climate, procurement planning and organizational anomie were significant predictors, accounting for 64% of the variance in ethical procurement behaviour. These results have both policy and managerial implications which we present and discuss in this paper.
Keywords: Psychological Climate; Catharsis; Organizational; Anomie; Psychological Wellness; Ethical Procurement Behaviour; Uganda's Public Sector